Globalization And Its Influence On Social Inequalities And Poverty Alleviation In Indonesia - Indah Maysa Amirtha; Timbul Dompak; Lubna Salsabila; Lenny Husna (International Journal of Social Science and Humanity, 2025)
Globalization has induced substantial changes across multiple facets of life in Indonesia, encompassing social, economic, and cultural dimensions. This study seeks to examine the effects of globalization on social inequality and poverty in Indonesia. The results demonstrate that globalization generates significant opportunities via access to global markets, foreign capital, and cutting-edge technologies. Nonetheless, these advantages are not uniformly allocated, leading to increasing societal inequalities. Communities possessing access to education, technology, and economic resources are more adept at leveraging globalization, but marginalized groups, such as the rural impoverished, often fall behind. Transformations in economic frameworks, urban development, and the impact of global culture intensify regional and socioeconomic disparities. While globalization can alleviate poverty via economic expansion, its advantages frequently favor particular demographics, therefore exacerbating the disparity between the affluent and the impoverished. This study underscores the significance of inclusive and equitable measures to alleviate the adverse effects of globalization. The government must improve access to education, technology, and economic opportunities for marginalized people while bolstering regional development to promote equality. Effective management of globalization can facilitate sustainable development and mitigate social inequality in Indonesia. Without sufficient action, globalization threatens to intensify inequalities and poverty within society.